1917 N.H. Laws 727-28, An Act for the Regulation of the Sale and Use of Explosives and Firearms, ch. 185, § 3 - (:unkn) unknown (General Publisher, 1917)
Every person so licensed shall keep, on blanks to be furnished by the secretary of state, a record of the names and residences of all persons to whom he shall sell or deliver firearms or any such explosive material or compound, the purpose of which the same is to be used¸ the date of sale, the amount paid, the date of the purchaser’s permit, the name and title of the person by whom the permit was issued, and, within five days after such sale or delivery, shall file such record thereof with the clerk of the city or town wherein he sale or delivery was made, or with the county commissioners in case of sales or deliveries within the state
--
Keywords: REGISTRATION